نظم تفسير سورة الفاتحة وشرحه - شكيمة, عبد القادر (جامعة الوادي - University of Eloued, 2023)
يتضمن هذا المقال شرح منظومة في تفسير سورة الفاتحة (النظم والشرح كلاهما لصاحب المقال)، بدأت النظم -ويتبعه الشرح- بمقدمة، ثم مهدت لنظم التفسير بنظم معاني الاستعاذة والبسملة، وقسمته إلى ثلاثة مباحث -على ضوء الحديث القدسي: " قسمت الصلاة بيني وبين عبدي نصفين ... " وعند الآية الرابعة قال: "هذه بيني وبين عبدي ..."-، الأول: نظمت فيه تفسير الآيات التي هي لله، والثاني: تفسير الآية التي هي بين العبد وربه، والثالث: تفسير الآيات التي هي للعبد، ثم ختمت المقال بنظم فوائد السورة. هذا ويهدف المقال إلى إبراز التفسير بشكل يجلب الانتباه؛ لأن النفوس مجبولة على حب النظم، ومن ثم رسوخ التفسير في الأذهان وإمكانية استحضاره في أي وقت إذا حفظ النظم وضبط في الصدر متنه وشرحه. This article includes an explanation of poetry in Surat Al-Fatihah, noting that the poetry and the explanation are both for the author of the article, and the exchange of ecosystems, and the like of his interpretation, his interpretation in his explanation, and its interpretation at that time and the basmalah, and I divided it into three sections according to the divine hadith: “I divided the prayer between me and my servant is two halves... and at the fourth verses he said: “This is between me and My servant...” - The first: He organized the interpretation of the verses that belong to Allah, the second: the interpretation of the verses that are between the servant and his God, and the third: the interpretation of the verses that belong to the servant, then I concluded the article with a poem about the benefits of the surah.
مقال
Keywords: نظم التفسير؛ الاستعاذة؛ البسملة؛ سورة الفاتحة؛ فوائد السورة; organize the interpretation; at that time; basmalah; Surat Al-Fatihah; the benefits of the surah.